Research on the Application Effects of Digital Transformation Strategies in Corporate Culture and Employee Engagement Cultivation - Lu, Yiqian; Xiong, Liubin (Journal of Global Economy, Business and Finance, 2025)
With the deep integration of next-generation information technologies such as artificial intelligence and big data, digital transformation has become a strategic imperative for enterprises to reconstruct their core competitiveness. This study focuses on the synergistic evolution mechanism between corporate culture and employee engagement in the context of digital transformation. Through a combination of theoretical analysis and case studies, it reveals the dual effects of digital transformation strategies in reshaping organizational culture and activating human capital. Key findings indicate that digital tools significantly promote the coupling development of culture and engagement through three pathways: digitized cultural symbol dissemination (23.6% increase in communication efficiency), data-driven employee behavior profiling (41.2% improvement in engagement assessment accuracy), and virtual collaboration space construction (35.8% boost in cross-departmental collaboration efficiency). However, challenges persist, including technology-induced emotional alienation (18.4% decline in employee belongingness), blurred data ethics boundaries (privacy concern index of 67.3), and intergenerational digital capability gaps (adaptation cycles for employees over 45 prolonged by 2.3 times). To address these issues, a three-dimensional “technology-culture-institution” optimization framework is proposed, advocating for the construction of a digital humanistic ecosystem, enhancement of data governance ethics, and implementation of tiered digital empowerment programs. This research provides theoretical foundations and practical pathways for enterprises to achieve organizational cultural continuity and human capital appreciation in the digital era.